2016
DOI: 10.1007/s10815-016-0751-z
|View full text |Cite
|
Sign up to set email alerts
|

Can Coenzyme Q10 supplementation protect the ovarian reserve against oxidative damage?

Abstract: Purpose We investigated antioxidant effects of CoQ10 supplementation on the prevention of OS-induced ovarian damage and to evaluate the protective effect of such supplementation against OS-related DNA damage. Methods Twenty-four adult female Sprague-Dawley rats were randomly divided into three groups (8 rats per group): group 1 (control): saline, ip, and orally; group 2 (cisplatin group): cisplatin, 4.5 mg/kg ip, two times with an interval of 7 days; and group 3 (cisplatin + CoQ10 group): cisplatin, 4.5 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 36 publications
(40 reference statements)
5
56
0
Order By: Relevance
“…As a result, a potent method to protect ovarian function would provide great benefits for patients and physicians. Many studies addressed the protection of ovarian function during cisplatin chemotherapy, but most of them involved antioxidants, such as coenzyme Q10, colony stimulating factor, sphingosine‐1‐phosphate, and erythropoietin (Akdemir et al, 2014; Dayangan Sayan et al, 2017; Li et al, 2014; Özcan et al, 2016; Roness, Kashi, & Meirow, 2016). However, the efficacy and specific mechanism of these drugs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a potent method to protect ovarian function would provide great benefits for patients and physicians. Many studies addressed the protection of ovarian function during cisplatin chemotherapy, but most of them involved antioxidants, such as coenzyme Q10, colony stimulating factor, sphingosine‐1‐phosphate, and erythropoietin (Akdemir et al, 2014; Dayangan Sayan et al, 2017; Li et al, 2014; Özcan et al, 2016; Roness, Kashi, & Meirow, 2016). However, the efficacy and specific mechanism of these drugs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous literatures indicated that when ovary is exposed to some drugs related to oxidative stress, such as chemotherapeutic drugs, gamma irradiation, or polycyclic aromatic hydrocarbons, loss of primordial follicles is induced. However, the mechanism of reactive oxygen species (ROS) causing primordial follicle depletion is not fully clear yet [ 17 19 ]. The mechanisms by which anticancer drugs exert cytotoxicity are diverse, and include the promotion of ROS generation.…”
Section: Introductionmentioning
confidence: 99%
“…Although shown to be beneficial in treating male oligo-asthenospermia and in cardiology, the clinical use in POR is not abundant (98)(99)(100)(101). Preclinical studies in animals have suggested CoQ10 can protect ovarian reserve, possibly counteracting the physiological ovarian aging by restoring mitochondrial function and augmenting embryo cleavage and blastocyst generation (102)(103)(104). In female infertility, CoQ10 supplementation to COH improved patients' response to ovulation induction and decreased fetal aneuploidy in older patients, between age 35 and 43 (105,106).…”
Section: Coenzyme Q10mentioning
confidence: 99%